SVIM Method: Metode Pengukuran Indikator Desa Cerdas - Eka Putra, I Gede Juliana; Wahyuni, Ni Wayan Dela (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
Smart Village or what is often called an intelligent village is a concept that encourages villages to transform through innovation by using technology. The aim is to improve the quality of services to the community through sustainable community empowerment. Smart village concept indicators involve various aspects of life starting from assessing the village economy, community, and government. Currently, the central and regional governments are focusing their attention on developing smart villages in several villages in provinces in Indonesia. The government through the Ministry of Villages, Development of Disadvantaged Regions and Transmigration has issued guidelines for villages to find out what things are of concern in realizing a smart village in a village, but in its implementation, several villages do not yet know how to carry out measurements and assessments related to the implementation of a smart village. In this regard, a framework for measuring smart village indicators is needed which can be used to measure the readiness of a village in developing a smart village program. The results of this research are in the form of a measurement framework that can be directly used by regional and village governments. The method used in this research is qualitative with descriptive analysis, data collection was carried out using interview and observation methods.